2017
DOI: 10.1111/bph.13892
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB1/CB2 receptor agonists attenuate hyperactivity and body weight loss in a rat model of activity‐based anorexia

Abstract: Taken together, our results further demonstrate the involvement of the EC system in AN pathophysiology and that strategies which modulate EC signalling are useful to treat this disorder, specifically in patients where physical hyperactivity plays a central role in its progression and maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
28
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 86 publications
(108 reference statements)
15
28
1
Order By: Relevance
“…Results of the recovery phase replicated our previously published data (Scherma et al, ). Specifically, ABA rats recovered to baseline body weight within the first 4 days of the recovery phase; however, at the end of this phase, their weight was significantly less than that of Control rats (Day 7: body weight Recovered ABA −6% vs. Control) [Two‐way ANOVA group × time interaction: F (7, 112) = 15.07, p < .0001; Figure ].…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Results of the recovery phase replicated our previously published data (Scherma et al, ). Specifically, ABA rats recovered to baseline body weight within the first 4 days of the recovery phase; however, at the end of this phase, their weight was significantly less than that of Control rats (Day 7: body weight Recovered ABA −6% vs. Control) [Two‐way ANOVA group × time interaction: F (7, 112) = 15.07, p < .0001; Figure ].…”
Section: Resultssupporting
confidence: 90%
“…For example, decreased 2‐AG levels and reduced CB1R expression in the Hipp of rats were found after chronic exposure to stress, suggesting that glucocorticoids exert a negative regulation over CB1R transcription (Hill et al, ). Consistent with this, we have recently shown increased corticosterone levels in the plasma of our individually housed ABA rats (Scherma et al, ). However, it is important to consider that a human PET study in vivo found that CB1R availability was globally increased in patients with AN compared with healthy control subjects (Gérard et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations